Development of Guar Gum-Pectin-Based Colon Targeted Solid Self-Nanoemulsifying Drug Delivery System of Xanthohumol - Mahesh Hanmantrao; Sourabh Chaterjee; Rajan Kumar; Sukriti Vishwas; Vancha Harish; Omji Porwal; Mohammed Alrouji; Othman Alomeir; Sharif Alhajlah; Monica Gulati; Gaurav Gupta; Kamal Dua; et al. (MDPI AG, 2022)
Present study deciphers development of oral polysaccharide-based colon targeted solid self-nanoemulsifying drug delivery system (S-SNEDDS) of xanthohumol (XH). Several studies have shown that XH has anti-inflammatory and antioxidant properties, suggesting that it could be a good candidate for the treatment of colorectal diseases (CRD). Despite its potential, XH has a low aqueous solubility. As a result, its bioavailability is constrained by the dissolution rate. The liquid (L)-SNEDDS was constituted using Labrafac PG as oil, Tween 80 as surfactant and Transcutol P as co-surfactant. The L-SNEDDS was then adsorbed onto the surface of guar gum and pectin and developed into S-SNEDDS powder. Ternary phase diagram was used to optimize the process of developing L-SNEDDS. The formulation showed mean droplet size of 118.96 ± 5.94 nm and zeta potential of −19.08 ± 0.95 mV and drug loading of 94.20 ± 4.71%. Dissolution studies carried out in medium containing rat caecal contents (RCC) represented the targeted release of S-SNEDDS powder. It was observed that S-SNEDDS showed less than 10% release XH in initial 5 h and rapid release occurred between the 5th and 10th hour. Results of cytotoxicity studies revealed good cytotoxicity of XH loaded S-SNEDDS for Caco2 cells as compared to raw-XH.